Experimental Phenomenology: Multistabilities - Ihde, Don 1934- (Albany, NY State University of New York Press, 2012)
Since the initial publication of 'Experimental Phenomenology' in 1977, Don Ihde's groundbreaking career has developed from his contributions to the philosophy of technology and technoscience to his own postphenomenology. This new and expanded edition of Experimental Phenomenology resituates the text in the succeeding currents of Ihdes work with a new preface and two new sections, one devoted to pragmatism and phenomenology and the other to technologies and material culture. Now, in the case of tools, instruments, and media, Ihdes active and experimental style of phenomenology is taken into cyberspace, science and media technologies, computer games, display screens, and more.
Keywords: 20th Century (1901-2000); Philosophy; Phenomenology; USA